Cold Urticaria, Immunodeficiency, and Autoimmunity Related to PLCG2 Deletions - Ombrello, Michael J; Remmers, Elaine F; Sun, Guangping; Freeman, Alexandra F; Datta, Shrimati; Torabi-Parizi, Parizad; Subramanian, Naeha; Bunney, Tom D; Baxendale, Rhona W; Martins, Marta S; Romberg, Neil; Komarow, Hirsh; et al. (The New England journal of medicine, 2012)
Analyses of families affected by cold urticaria, immunodeficiency, and autoimmunity implicate mutations that activate phospholipase Cγ2 (PLCγ2), an enzyme pivotal to the translation of binding events at the cell surface to the intracellular milieu, as a cause of the disease. The genetic dissection of unique inflammatory phenotypes can identify and elucidate immunologic pathways and mechanisms. Such investigations have ultimately led to findings whose significance extends beyond the monogenic diseases harboring the mutations. Examples include the recognition that FOXP3 is essential for the differentiation of regulatory T cells in Scurfy mice and in patients with profound immune dysregulation, 1 – 4 the demonstration of a critical role for AIRE in thymic negative selection of T cells in patients with a specific autoimmune polyendocrinopathy, 5 and the identification of NLRP3 as a critical regulator of interleukin-1 in families with cold-induced inflammation. 6 Cold-induced urticaria is a . . .